Assessing the Impact of Out-of-Pocket Expenditures for Prevention of COVID-19 Infection on Households: Evidence From Malaysia - Mohd Hafiz Jaafar; Nur Amalina Abd Laziz; Muslimah Ithnin; Amirah Azzeri (SAGE Publications Inc., 2024)
Indexed by Scopus